Strengthening the Financial Components of State Regulation of Agricultural Production in Ukraine - Lesia BARABASH; Alla OSIPOVA; Irina KORMAN; Natalia OLYADNICHUK; Oksana FROTER (Communications of International Proceedings, 2020)
State regulation of agricultural production is an essential component of state financial and economic mechanisms, due to the importance of the agricultural sector as a basic source of food security. However, for the purposes of state regulation of this industry, Ukraine has followed the other way from developed countries, as direct government financial support was directed not to medium and small agricultural formations, but to large enterprises and agricultural holdings. As a result of such a regulatory policy, Ukraine is currently experiencing a deterioration in the quality of land, declining quality of agricultural products, misbalance in the development of agricultural production, rising unemployment and impoverishment in rural areas. As a result, Ukraine's agricultural sector is unattractive to investors, which hinders its harmonious and sustainable development. The analysis of the functioning of the current system of state regulation of agricultural production testified to its inefficiency and the need to find areas for improvement. Therefore, attention was drawn to the need to activate the financial levers to stimulate the development of agricultural production, in particular its small forms: personal farms, farms and more. To increase interest and the level of efficiency of state regulation of agricultural production, a combined mechanism of state regulation of small agricultural producers, based on the use of products of financial components such as lending, insurance and taxation.
Keywords: State Regulation; Agricultural Production; Microinsurance; Microcredit.